2018
DOI: 10.1177/2397198318779532
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory arthritis in systemic sclerosis: What to do?

Abstract: Musculoskeletal involvement, including arthritis and tendinopathy, is a common and important determinant of disability and impaired quality of life in systemic sclerosis. However, the treatment of arthritis in systemic sclerosis has not been studied as a primary outcome in randomized controlled trials, and arthritis-specific outcome measures for systemic sclerosis have not been sufficiently validated to date. Rheumatologists caring for patients with systemic sclerosis must address these complaints regularly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 89 publications
0
7
0
1
Order By: Relevance
“…The individual reductions in the TOF group varied within a larger range (− 0.12 mm to 0.57 mm) versus − 0.02 mm to − 0.17 mm in the MTX group. Musculoskeletal US may be used to assess articular and periarticular involvement in SSc patients [38][39][40][41]. Elhai et al showed that signs of tendon involvement were more frequent in SSc than in RA patients [42].…”
Section: Discussionmentioning
confidence: 99%
“…The individual reductions in the TOF group varied within a larger range (− 0.12 mm to 0.57 mm) versus − 0.02 mm to − 0.17 mm in the MTX group. Musculoskeletal US may be used to assess articular and periarticular involvement in SSc patients [38][39][40][41]. Elhai et al showed that signs of tendon involvement were more frequent in SSc than in RA patients [42].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems that in order to determine the severity of the locomotor system involvement more objectively, the scales for the assessment of pSS activity, i.e. SDAI, CDAI, DAS28–CRP or DAS28–ESR, that are also reliable in the assessment of arthritis in the course of SSc, should be used [ 51 , 52 ].…”
Section: Methods Of Assessment Of Joint Involvement In the Course Of ...mentioning
confidence: 99%
“…Data from our single tertiary care centre showed that the prevalence of any contracture (defined as more than a 25% decrease in the range of motion in any of the joint axes) was 82% (9). Arthritis predominantly affects the joints of the hands and usually appears early in the disease course of SSc (1,8,(10)(11)(12), resulting in contractures which are one of the primary causes of disability and poor quality of life in patients with SSc (13)(14)(15). The newly developed Scleroderma Clinical Trials Consortium Damage Index (SCTC-DI) includes joint contractures as part of musculoskeletal damage (16).…”
Section: Introductionmentioning
confidence: 99%